2021
DOI: 10.3390/nu13020304
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Functional Dysbiosis Relates to Individual Diet in Subclinical Carotid Atherosclerosis

Abstract: Gut Microbiota (GM) dysbiosis associates with Atherosclerotic Cardiovascular Diseases (ACVD), but whether this also holds true in subjects without clinically manifest ACVD represents a challenge of personalized prevention. We connected exposure to diet (self-reported by food diaries) and markers of Subclinical Carotid Atherosclerosis (SCA) with individual taxonomic and functional GM profiles (from fecal metagenomic DNA) of 345 subjects without previous clinically manifest ACVD. Subjects without SCA reported co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 68 publications
0
24
0
1
Order By: Relevance
“…In recent years, several studies have confirmed the presence of bacterial DNA in atherosclerotic plaque which may contribute to the development of cardiovascular disease (52). In addition, researchers have also found that compared with people without atherosclerosis, the patients with atherosclerosis (Table 1) showed some differences in the gut microbiota (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)53). Garshick et al donated aortas of Apoe-/-mice with atherosclerosis into normolipidemic wild-type mice, then feeding antibiotic.…”
Section: Microbiota and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have confirmed the presence of bacterial DNA in atherosclerotic plaque which may contribute to the development of cardiovascular disease (52). In addition, researchers have also found that compared with people without atherosclerosis, the patients with atherosclerosis (Table 1) showed some differences in the gut microbiota (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)53). Garshick et al donated aortas of Apoe-/-mice with atherosclerosis into normolipidemic wild-type mice, then feeding antibiotic.…”
Section: Microbiota and Atherosclerosismentioning
confidence: 99%
“…In recent years, several studies have investigated the effects of the gut microbiota on atherosclerosis and proved that there are some connections between cardiovascular events and atherosclerotic plaque characteristics (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, the roles of the gut microbiota in the stability of plaque are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota is involved in the metabolism of dietary sources and rapidly varies according to dietary habits [86]. A growing number of animal and human studies [45,70,[72][73][74][75]87,88] have reported a close relationship between dietary patterns, gut microbiota, the formation of microbiota-derived metabolites such as TMAO and the development of cardiovascular diseases (Table 6).…”
Section: Diet Microbiota and Cadmentioning
confidence: 99%
“…Thus, gut microbiota γBB→TMA/TMAO transformation may induce by omnivorous dietary patterns and chronic l-carnitine exposure [72]. A recent study of 345 adults found that in adults with SCA compared with those without SCA, higher levels of Escherichia coli were shown as well as an increased TMAO production [70]. E. coli also correlated with increased LPS absorption and macrophage activation.…”
Section: Diet Microbiota and Cadmentioning
confidence: 99%
“…All research was conducted under the U.K. home office project license number: 70/8350. Human samples for LL-37 determination were obtained from subjects participating in the Progressione delle Lesioni Intimali Carotidee (PILC) project, which has been extensively described elsewhere (16)(17)(18). Subjects of this study were screened at the Center for the Study of Atherosclerosis at E. Bassini Hospital (Cinisello Balsamo, Milan, Italy) for personal and familial clinical history of T2DM [defined according to validated criteria (19,20) and as previously described ( 21)].…”
Section: Ethical Statementmentioning
confidence: 99%